Inflation, Operational Efficiency Ratio and Non-Performing Financing on Muamalat Bank Profitability - Wandirah, Ayu; Musthofa, Muhammad Wakhid (Yayasan Cita Cendekiawan Al Khwarizmi, 2023)
This research aims to determine the effect of inflation, operational efficiency ratio (OER), as well non-performing financing (NPF) on profitability at Bank Muamalat in 2019-2022. This research includes quantitative research, using secondary data in the form of a time series namely Bank Muamalat financial publication report as a sample. Data analysis was carried out using the concept of multiple linear regression using the method of Ordinary Least Square (OLS). The results of testing and data analysis using EViews version 12 software show that partial inflation and NPF do not affect Bank Muamalat profitability, while OER has a significant effect on Bank Muamalat profitability, indicating that the direction of this influence is negative. This shows that during the observation period (2019-2022) Bank Muamalat had a low OER ratio, so the bank was able to generate profits, the relationship was significantly negative because increasing OER could reduce Bank Muamalat profitability ratio.